Implementing social security programs for employees in Bandar Lampung: Challenges and recommendations - Rahma, Siti; Triono, Agus; A.T., Marlia Eka Putri (Goodwood Publishing, 2023)
Purpose: The purpose of this study was to determine the application of the Sosial Security Program/Jaminan Hari Tua (JHT) program and the factors inhibiting the JHT program. Research methodology: This study is a type of Normative Juridical and Empirical Juridical research. Normative jurisdictional research is carried out based on legal materials such as legal theory, legal principles, and legislation related to research. Meanwhile, empirical juridicals were conducted through interviews. A qualitative analysis was performed. Results: The results of this research show that JHT has been implemented in accordance with Government Regulation Number 46 of 2015 concerning the Implementation of the Old Age Security Program. Article 22 states that the JHT can be withdrawn when fulfilling the requirements with a minimum participation period of 10 years. However, in reality, this has generated pros and cons because the JHT can only be cashed out at the age of 56. This can be detrimental to JHT participants who are not yet 56 years old but need to withdraw funds immediately. Limitations: The Social Security Organizing Agency (BPJS) has an Old Age Insurance Program (JHT) that guarantees workers to receive cash when entering retirement, experiencing total disability, and death. However, despite experiencing these conditions, JHT disbursements have obstacles when disbursing money. Contribution: Therefore, the BPJS should improve the JHT system and conduct socialization to overcome the lack of information related to JHT disbursement.